Morphology-tunable synthesis of ZnO microstructures under microwave irradiation: formation mechanisms and photocatalytic activity. Issue 6 (14th January 2016) - Kim, Hyung-Bae; Jeong, Dong-Won; Jang, Du-Jeon
Abstract : The microwave-assisted fabrication and the photocatalytic application of porous burger-like ZnO twin microstructures are presented. Abstract : The morphologies and surface conditions of ZnO microstructures have been controlled facilely via a microwave-assisted one-pot synthetic route by varying the ammonia concentration of the reaction mixture. Ammonia affects the nucleation, growth, and hydrolysis kinetics of a zinc glycerolate intermediate to induce shape variation from flower-like ZnO microstructures to various ZnO twin microstructures with a preferred exposure of ± (0001) polar planes. The as-prepared ZnO microstructures are mesoporous, as they have large specific surface areas and high specific pore volumes that have resulted from the microwave-assisted fast hydrolysis of the zinc glycerolate intermediate microstructures. Owing to the novel features of microwaves, the ZnO microstructures have numerous microcracks and wrinkles on their surfaces and show characteristic defect-driven orange emission, whose intensity increases with the specific surface area. The photocatalytic degradation rate constant of rhodamine B via our prepared ZnO microstructures has been found to increase linearly with the specific surface area, the specific pore volume, and the polar-surface exposure. Our simple and rapid microwave-assisted synthetic method is considered to be beneficial to the development of morphology-controlled metal oxides that are applicable for eco-friendly waste-water treatments.